Simplifying The Blue Economy for Msmes in the Riverbank and Coastal Areas of Kerobokan, Buleleng: A Sustainable Approach to Community Empowerment - SAPUTRA, Komang Adi Kurniawan; LAKSMI, Putu Ayu Sita; SANCAYA, I Wayan Werasmana; PRAMAISWARI, Made Adinda Anugrah Deva; PRATIKA, I Gede Candra Adi (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to empower MSMEs in the riverbank and coastal areas of Kerobokan, Buleleng, through the application of a simplified blue economy concept. The program was implemented for 8 months and involved 20 MSMEs from the "Rukun Sejati" Joint Business Group engaged in fisheries and egg-laying chicken farming. The methods used included three main approaches: (1) education through interactive workshops on blue economy principles, (2) technical assistance in processing waste into value-added products (organic fertilizer, fish bone chips), and (3) strengthening digital marketing through collaboration with PT KSI. The evaluation results showed an increase in understanding of the blue economy concept from 33% to 67%, a 40% reduction in organic waste in rivers, and an average increase in MSME income of 25% through product diversification and online marketing. The main challenges faced included resistance to change, limited digital infrastructure, and dependence on external assistance. The program succeeded in creating an empowerment model that integrates economic, social, and environmental aspects, with key recommendations being the formation of a permanent working group and the development of advanced training modules. These findings provide practical contributions to the development of sustainable coastal MSMEs and can serve as a reference for replication in areas with similar characteristics.